Maßgeschneiderte Werkstoffcharakterisierung für die numerische Auslegung von Blechumformprozessen - Lenzen, Matthias (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)
In many industries, there is a trend towards lightweight design to reduce the overall weight of the product. The challenge in this context is the reduced formability of these innovative materials with lightweight design potential. Especially the material behavior at plane strain is of crucial importance, since the lowest formability is present here. The primary objective is therefore the fundamental investigation of the material behavior at plane strain and the influence on the mapping accuracy of the modeled yield locus in the context of plane strain. For this purpose, new testing and evaluation methods are being developed. The resulting material parameters will subsequently be used for an improved modeling. The approach will be validated by means of error indicators based on a sample process. The aim is to achieve an efficient material characterization and identification of the essential model parameters in order to improve the simulation quality. With the knowledge gained, it is possible to reduce the number of tests required and thus the financial and time expenditure to the necessary minimum, while at the same time making the process design more efficie